INVENTARISASI HEWAN INVETEBRATA PADA FILUM NEMATHELMINTHES - RAHMADINA RAHMADINA; FAJAR RENALDI (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
This journal discusses the theme of the Nemthelminthes phylum. nemathelminthes is a phylum that was once used in the animal kingdom (Animalia). Its members include a variety of worms known as gilig worms: animals with long cylindrical bodies, even so long that the name 'Nemathelminthes' appears. Which means